Akal Bertingkat Ibnu Sina dan Taksonomi Bloom dalam Pendidikan Islam Perspektif Neurosains - Kharisma Noor Latifatul Mahmudah; Suyadi (Edukasia Islamika : Jurnal Pendidikan Islam, 2020)
This study aims to analyze the concept of Ibn Sina’s multilevel sense and its correlation with Bloom's Taxonomy in Islamic education from the perspective of neuroscience. This study belongs to qualitative approach and uses library research. The data source of this study is all kinds of literature related to Islamic education especially Ibn Sina's multilevel sense, Bloom's Taxonomy as well as neuroscience. The data were obtained through collecting some relevant literatures both printed and online one. The collected data then analyzed by using content analysis, started from data reduction, display data, up to become new concept construction. The result of this study shows that there is an interdisciplinary study between Islamic education and neuroscience as well as Ibn Sina’s multilevel sense with Bloom's Taxonomy. Ibn Sina’s concept of hierarchy provides stages of thinking started from the empirical, theoretical, and philosophical up to metaphysical. In other words, it provides the rational way of thinking up to suprarational. It is in line with Bloom's Taxonomy containing the low level of thinking up to high order thinking skills. Therefore, Ibn Sina’s multilevel sense can be used as a new alternative learning taxonomy of Islamic education which is believed to be more potential and relevant with the brain performance in neuroscience studies